Focal loss volume of ganglion cell complex in diabetic neuropathy. (29th March 2016) - Srinivasan, Sangeetha; Pritchard, Nicola; Sampson, Geoff P; Edwards, Katie; Vagenas, Dimitrios; Russell, Anthony W; Malik, Rayaz A; Efron, Nathan
Abstract: Background: The aim was to investigate the relationship between diabetic peripheral neuropathy (DPN) and abnormalities in ganglion cell complex (GCC); specifically, focal loss volume (FLV) and global loss volume (GLV). Methods: The ganglion cell complex was evaluated using optical coherence tomography on 193 individuals (84 with type 1 diabetes, 67 with type 2 diabetes and 42 without diabetes). In those with diabetes, 88 had diabetes but no diabetic retinopathy (no DR group) and 63 had diabetes with diabetic retinopathy (DR group). Seventeen individuals in the no DR group and 27 in the DR group had diabetic peripheral neuropathy according to the neuropathy disability score (NDS). The probability of FLV and GLV being abnormal was determined. Forty four individuals had diabetic peripheral neuropathy (NDS of three or greater). Binary logistic regression analysis was performed, adjusting for the presence of diabetic retinopathy, age, sex, type of diabetes, duration of diabetes and HbA1c levels. Results: Twenty‐five per cent of individuals with diabetic peripheral neuropathy had abnormal FLV compared to 11 per cent of those with diabetes but no diabetic peripheral neuropathy and five per cent in the control group (p = 0.011). Fourteen per cent of individuals with diabetic peripheral neuropathy, 10 per cent without diabetic peripheral neuropathy and two per cent in the control group had abnormal GLV (p = 0.185). For every unit increase in the neuropathy disability score, the odds of having an abnormal FLV increased by a factor of 1.25 (p = 0.007), after adjusting for potentially confounding factors. Abnormal GCC FLV is an independent predictor of diabetic neuropathy, (odds ratio = 2.94, 95 per cent CI [1.16, 7.40], p = 0.023). Conclusion: Diabetic peripheral neuropathy is associated with abnormal GCC FLV at the macula, which is independent of diabetic retinopathy, age, sex, type of diabetes, duration of diabetes and HbA1c levels. An abnormality in GCC FLV is an independent predictor of diabetic peripheral neuropathy.